Dasya enomotoi sp. nov. (Dasyaceae, Ceramiales), a new large Dasya from Japan. Issue 1 (7th November 2013) - Yamagishi, Yukimasa; Ohta, Yusuke; Masuda, Michio; Abe, Tsuyoshi
Summary A new red alga, Dasya enomotoi, is described from Japan. This species is characterized by having a large thallus consisting of an elongated axis and many, radially arranged, polysiphonous branches both of which are heavily corticated and densely covered with numerous, soft monosiphonous filaments. It is distinguished from several similar species by the combination of the following: (i) indistinct pericentral cells in transverse sections except near the apices, (ii) the presence of enlarged, inner cortical cells, (iii) radially arranged adventitious monosiphonous filaments, (iv) three‐celled carpogonial branches, (v) six (sometimes five) tetrasporangia in each fertile segment of the stichidia, and (vi) three tetrasporangial cover cells that are not elongated longitudinally and usually not divided transversely. This species may have been identified as D. villosa Harvey by previous investigators in Japan.